Systematized review: Isokinetic evaluation in the assessment of upper extremity sports - Matías González; Belén Montoya; Aníbal Jiménez; Martin Salazar; Esteban Aedo Muñoz; Bianca Miarka; David Arriagada-Tarifeño (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: A systematized review was carried out to identify the studies that during the last ten years have used isokinetic equipment in sports in which the upper extremity is the basis of its practice, to provide an updated and detailed view of its use, methodologies and the variables used to express their results. Methods: A systematized search of 10 years of information was carried out, according to the PRISMA process, in the databases: Scopus, Web of Science, Pubmed, CINAHL, using combined terms: «isokinetic» «upper extremity», «upper limb», « sport», «exercises», «upper extremity». Results: 9406 articles were identified in the databases for review, of which only 46 were selected based on inclusion criteria. Among the sports evaluated, 25 articles correspond to sports with overhead throws (basketball, volleyball, baseball, handball, among others), followed by Paralympic sports with six articles (basketball and volleyball). Sports such as swimming, judo, weightlifting, water polo, or combined sports complete the list. The shoulder rotator muscles were the most evaluated and the concentric-concentric modality was the most used. The variable moment is the most reported, but the evaluation methodologies and selected speeds differ significantly between studies. Conclusion: The methodologies used are varied (i.e., selection of speed, type of muscular contraction, positioning, and dominance), and their selection was not always oriented toward the functionality of sports practice. In addition, it was observed that some studies needed to specify the isokinetic modality used, leaving a gap in relevant information within the study methods and affecting their future replicability.